Political agreements in the resolution of internal armed conflicts in Africa - (:unkn) unknown (My University, 2011)
Since some decades, Africa is «the most destabilized strategic area of the plane. » the issue of armed conflicts represent a real «African puzzle» as well for local actors as international ones who are involve in, with its internal characteristic contrast with the transnational consequences which result from.How to get out of this chronically in security and the civil war which permanently watch out behind curtain in order to reach sustainable development and stability in order to better limit numerous violations of human rights done in that fact?Some approaches of solution are numerous, going from military solution less respecting human lives, to the negociated solutions which call for the human genius and his intelligent, anxious to preserve human gender by «imaging» or by « inventing» Compromises signed in agreements, essentially political. Its then, precisely that African issue translated by an updated heading: agreements in the resolution of internal armed conflits in Africa. »The analysis considered in the present study will expose the conclusion of political agreements by insisting distinctly on political environment, their formation as well on the legal framework which characterizes them, on one hand. On the other hand, it seems important to examine the application of those agreements by analyzing in details the agenda in which they evoluate in order to draw up scientifically the balance sheet of the objective in order to assess the affectivity of their implementation and their effectiveness in domain of human rights protection.
Keywords: African Research